The use of an interactionist model for the teaching practice analysis - Fragoza González, Ariana (2018)
The present essay has the purpose of describing the E-P-R Model (Epistemological-Pragmatic-Relational). This model is a theoretical-methodological reference used for the training of teachers, from a reflective perspective. The main author is Isabelle Vinatier. The E-P-R model is based on theoretical elements that come from the psychological and sociological discipline. For the analysis of teaching practice, the E-P-R model provides three theoretical categories, which refer to the dimensions present in the teaching practice simultaneously: the Epistemological, Pragmatic and Relational (responds to the acronym E-P-R of the model). The reflexive exercise about the teaching practice gives guidelines to deepen questions such as: How have the actions been carried out? Why are things done this way and not another? and What does it mean for the teacher? This series of questions can set the tone for the teacher to improve their practice by becoming a conscious subject about their own actions. In Mexico, training experiences with basic education teachers using the EPR model evidenced that the model strengthens teachers as subjects, as competent professionals, providing a self-evaluating perspective and criticism about his practice and that of his colleagues.